Antioxidant properties of selected non-leafy vegetables - Ismail, Amin; Tiong, Ngee Wen; Tan, Seok Tyug; Azlan, Azrina (Emerald Group Publishing, 2009)
Purpose: The purpose of this paper is to determine the antioxidant properties (capacity and component) of four non-leafy vegetables. The correlation between the antioxidant capacity and its components of the studied vegetables was also assessed.